Football's Irish exodus: Examining the factors influencing Irish player migration to English professional leagues1. (March 2016) - Elliott, Richard
The intention of this paper is to examine the range of interdependent processes that influence the decisions of Irish footballers to migrate from teams based in the League of Ireland to English Premier League and Football League clubs. Using data derived from a series of qualitative interviews conducted with a group of Irish players that had relocated to English clubs at different points over a 20-year period, the analysis reveals that the players' decisions to migrate are predicated upon the interdependency of a number of processes that push the migrants from Ireland and pull them to England. The paper shows how these processes are reflected in a series of migrations where the players are not simply passive social agents but, rather, dynamic interlocutors whose decisions must be framed within the local contexts between which their movements are situated.